The seventh cervical vertebra is an appropriate landmark for thoracic kyphosis measures using distance from the wall - Arpassanan Wiyanad; Sugalya Amatachaya; Pipatana Amatachaya; Patcharawan Suwannarat; Pakwipa Chokphukiao; Thanat Sooknuan; Chitanongk Gaogasigam (World Scientific Publishing, 2023)
Background: Hyperkyphosis is frequently found nowadays due to the change in current lifestyles and age-related system decline. A simple hyperkyphosis measurement can be made easily using the perpendicular distance from the landmark to the wall. However, the existing evidence applied two different landmarks [occiput and the seventh cervical vertebra (C7)] and the measurement using rulers was susceptible to error due to their misalignment. Objective: To assess an appropriate landmark for thoracic kyphosis measurement using distance from the wall (KMD), by comparing between occiput and C7, as measured using rulers and verified using data from a specially developed machine, the so-called infrared-gun kyphosis wall distance tool (IG-KypDisT), and the Cobb angles. Methods: Community-dwelling individuals with a risk of thoracic hyperkyphosis (age [Formula: see text] years, [Formula: see text]) were cross-sectionally assessed for their thoracic hyperkyphosis using the perpendicular distance from the landmarks, occiput and C7, to the wall using rulers and IG-KypDisT. Then the Cobb angles of these participants were measured within seven days. Results: The outcomes from both landmarks differed by approximately 0.8[Formula: see text]cm ([Formula: see text] 0.084). The outcomes derived from C7 were more reliable (ICCs[Formula: see text]0.93, [Formula: see text]0.001), with greater concurrent validity with the radiologic data ([Formula: see text] 0.738, [Formula: see text]0.001), with the overall variance predicted by the regression models for the Cobb angles being higher than that from the occiput (47-48% from C7 and 38-39% from occiput). The outcomes derived from rulers and IG-KypDisT showed no significant differences. Conclusion: The present findings support the reliability and validity of KMD assessments at C7 using rulers as a simple standard measure of thoracic hyperkyphosis that can be used in various clinical, community, and research settings.